Program Kemitraan Kemasan Untuk Meningkatkan Daya Saing UMKM Di Makale Tana Toraja - Stefani M. Palimbong; Isak Pasulu (Pusat Riset dan Inovasi Nasional, 2021)
The Packaging Partnership Program is an initiative that aims to increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs) through improving the quality of product packaging. Attractive and functional packaging is the key to attracting consumer interest and increasing market share. This program is carried out through a series of activities, including education, training, design assistance, introduction of environmentally friendly packaging materials, testing, evaluation, implementation and product promotion. Through this program, MSMEs can increase their competitiveness in the market, increase sales, increase environmental awareness, and gain new knowledge and skills in designing product packaging. Collaboration between government, non-profit institutions and the private sector is the key to success in supporting MSMEs and encouraging inclusive economic growth.